2019
DOI: 10.1111/ejh.13284
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgical thrombotic microangiopathy: Case series and review of the literature

Abstract: Objectives Describe the clinical presentation, treatment, and outcomes of postsurgical thrombotic microangiopathy (TMA). Methods In this retrospective study, records of individuals diagnosed with TMA developing within 30 days of a surgical procedure at Mayo Clinic from 2000 to 2016 were reviewed. Available literature regarding postsurgical TMA was comparatively reviewed. Results Twenty patients were diagnosed with TMA developing within 30 (median 6.5, range (1‐28)) days) following a procedure. Preceding proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…It has not yet been established why surgery-associated TTP resembling classical TTP can occur even though ADAMTS-13 activity is only moderately reduced. Nor has the clinical relevance of mildly reduced intraoperative and postoperative ADAMTS-13 activity been clarified 24 ; no patient in this study showed clinical appearance of TTP. These findings may suggest that the level of ADAMTS-13 activity is not the only essential factor in the development of surgery-associated TMA.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…It has not yet been established why surgery-associated TTP resembling classical TTP can occur even though ADAMTS-13 activity is only moderately reduced. Nor has the clinical relevance of mildly reduced intraoperative and postoperative ADAMTS-13 activity been clarified 24 ; no patient in this study showed clinical appearance of TTP. These findings may suggest that the level of ADAMTS-13 activity is not the only essential factor in the development of surgery-associated TMA.…”
Section: Discussionmentioning
confidence: 70%
“… 14 Recent investigations could not detect any appearance of new inhibitory ADAMTS-13 antibodies after cardiac surgery. 6 In contrast to these findings, Sridharan et al 24 identified 2 of the patients in their institutional review with immune-mediated pTTP. In both reviews, cardiovascular and vascular surgery were identified as the most common procedures leading to pTTP.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations